2018
DOI: 10.1016/j.econlet.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Long Memory Interdependency and Inefficiency in Bitcoin Markets

Abstract: We model cross-market Bitcoin prices as long-memory processes and study dynamic interdependence in a fractionally cointegrated VAR framework. We find (i) long-memory in both individual market and five-market systems depicting non-homogeneous informational inefficiency and (ii) a cointegration relationship with slow adjustment of shocks where uncertainty leaves a negative impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(89 citation statements)
references
References 19 publications
3
81
0
1
Order By: Relevance
“…More recently, Brauneis and Mestel [2018] extended the existing literature on the efficiency of cryptocurrency markets by performing various tests on efficiency of several cryptocurrencies, and additionally linked efficiency to measures of liquidity when the authors found that cryptocurrencies become more efficient as liquidity increases. On the other hand, the studies of Jiang et al [2017] and Cheah et al [2018] found contradictory results to those listed above. More specifically, in an attempt to examine the time-varying long-term memory in the Bitcoin market through a rolling window approach and by employing the efficiency index of Sensoy andHacihasanoglu [2014], Jiang et al [2017] found a high degree of inefficiency ratio and that the Bitcoin market does not become more efficient over time.…”
Section: Previous Literaturementioning
confidence: 72%
See 1 more Smart Citation
“…More recently, Brauneis and Mestel [2018] extended the existing literature on the efficiency of cryptocurrency markets by performing various tests on efficiency of several cryptocurrencies, and additionally linked efficiency to measures of liquidity when the authors found that cryptocurrencies become more efficient as liquidity increases. On the other hand, the studies of Jiang et al [2017] and Cheah et al [2018] found contradictory results to those listed above. More specifically, in an attempt to examine the time-varying long-term memory in the Bitcoin market through a rolling window approach and by employing the efficiency index of Sensoy andHacihasanoglu [2014], Jiang et al [2017] found a high degree of inefficiency ratio and that the Bitcoin market does not become more efficient over time.…”
Section: Previous Literaturementioning
confidence: 72%
“…Studies of the market efficiency of cryptocurrencies include those of Urquhart [2016], Bariviera et al [2017], Nadarajah and Chu [2017], Brauneis and Mestel [2018], Cheah et al [2018], Khuntia and Pattanayak [2018], Sensoy [2018], Tiwari et al [2018], and Vidal-Tomás and Ibañez [2018], among others. More specifically, in an early study of the efficiency of Bitcoin, Urquhart [2016] used a battery of robust tests to find that Bitcoin returns are significantly inefficient over their selected full sample, but when dividing the same sample, Bitcoin presented evidence of becoming more efficient.…”
Section: Previous Literaturementioning
confidence: 99%
“…Scientists belonging to the first of these groups are of the opinion that the cryptocurrency market meets the tenets of the efficient market hypothesis - Brauneis and Mestel (2018), Nadarajah and Chu (2017), Vlasov and Demin (2017), Tiwari (2018), Bariviera (2017), Sensoy (2018). However, researchers from the other group, most of whom have conducted their studies relatively recently, express the opposite view -for example, Cheah (2018) or Yonghong (2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…O uso das criptomoedas proporciona às empresas o acesso potencial a novas tecnologias, mas também expõe a empresa a riscos adicionais, dentre eles, estão: volatilidade do preço, futura legislação, roubo ou perda e confiabilidade de terceiros (GRANT; HOGAN, 2015). Quanto a estudos envolvendo a volatilidade, percebe-se que os investidores são atraídos após grande taxa de volatilidade e volumes de negociação (URQUHART, 2018), bem como utilizam a memória estimada para capturar lucros especulativos (CHEAH et al, 2018). Já para as situações de roubo e/ou perda da criptomoeda, em que o investidor não consegue rastreá-la nem possui à sua disposição qualquer mecanismo para recuperá-la, percebe-se que, embora o anonimato seja defendido como uma forma de privacidade para os clientes, ocasiona riscos maiores (DOSTOV; SHUST, 2014).…”
Section: Criptomoedas E Investimentosunclassified